Non-coding RNA-mediated granulosa cell dysfunction during ovarian aging: From mechanisms to potential interventions - Li Dong; Haicui Wu; Fanghua Qi; Yuan Xu; Wen Chen; Yuqi Wang; Pingping Cai (Non-coding RNA Research)
As the earliest aging organ in the reproductive system, the ovary has both reproductive and endocrine functions, which are closely related to overall female health. The exact pathogenesis of ovarian aging (OA) remains incompletely understood, with granulosa cells (GCs) dysfunction playing a significant role in this process. Recent advancements in research and biotechnology have highlighted the importance of non-coding RNAs (ncRNAs), including micro RNAs, long non-coding RNAs, and circular RNAs, in regulating the biological functions of GCs through gene expression modulation. This paper provides a comprehensive overview of the role of ncRNAs in various cellular functions such as apoptosis, autophagy, proliferation, and steroid synthesis in GCs, and explores the underlying regulatory mechanisms. Additionally, the therapeutic potential of ncRNAs, particularly those carried by exosomes derived from mesenchymal stem cells, in delaying OA is discussed. Understanding the regulatory mechanisms of ncRNAs in GC function and the current progress in this field is crucial for identifying effective biomarkers and therapeutic targets, ultimately aiding in the early diagnosis, prognostic assessment, and individualized treatment of OA.